The Impact of Advertising on the Popularity of Music Works - Dehghaninasrabad, Hamed (International Journal of Scientific Research and Management (IJSRM), 2024)
Not only is advertising a powerful tool for businesses and marketing, it also shapes consumers’ behavior in the music industry as well.This article deals with the influence of traditional and digital advertising methods on the popularity of musical productions.This research seeks to navigate the relationship between the intensity of advertising and the popularity of the music work through the examination of several case studies and data from different genres of music. It highlights the roles of several media channels and platforms including streaming services and social media in making songs go viral as well as the economic impacts on the musicians and record companies.The study provides insight into the problem of excessive commercialization in a digital sphere as a consequence of modern overexposure of the music industry.This article concludes with recommendations for maximizing the effects of advertising on musical productions’ popularity while maintaining artistic integrity.